Identifikasi Bahaya dan Penilaian Risiko Ergonomi Petani Padi Dusun Gugur, Kecamatan Matesih, Kabupaten Karanganyar - Nabylla Sharfina Sekar Nurriwanti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The agricultural sector is an informal sector that often does not receive full attention regarding occupational safety and health. One of the common hazards found in the informal sector is ergonomic hazards. This study aims to identify hazards and assess ergonomic risk among rice farmers in Dusun Gugur, Matesih Subdistrict, Karanganyar Regency. The study was conducted from August to December 2024 using a descriptive observational method with a cross-sectional time approach. The sample consisted of 20 rice farmers selected using accidental sampling. Primary data were collected through focus group discussions and direct field observations. The hazard identification results showed that the most dominant ergonomic risks included prolonged bending postures, repetitive body movements, and the frequent carrying of heavy loads during work. Based on the risk assessment, most farming activities were categorized as high ergonomic risk. These findings highlight the need for ergonomic interventions to reduce the risk of musculoskeletal disorders, which can impact the health and productivity of farmers.